Kapasitas Adaptif Petani Menghadapi Perubahan Iklim: Studi Terhadap Masyarakat Petani di Kabupaten Brebes - Rustian, Rustian; Fikri, Ahmad Fatkul; Mohammad Afifuddin (Universitas Islam Negeri Sunan Ampel, 2025)
Climate change increases risks for the agricultural sector through shifting rainfall patterns, prolonged dry seasons, and rising average temperatures that reduce production. These conditions demand strong adaptive capacity among smallholder farmers, yet studies on their strategies remain limited. This research aims to analyze the adaptive capacity of rural farmers in responding to climate change. A qualitative approach was employed through in-depth interviews using purposive sampling in five districts of Brebes Regency (5–9 participants per site), with data analyzed using NVivo 12. Findings show that farmers rely on local knowledge, such as reading natural signs to determine planting times, and technical skills in water management and cultivation practices. Adaptation also includes the use of water pumps, drought-resistant seeds, and weather-based mobile applications, although access to technology remains limited. Collaborative capacity is reflected in partnerships with agricultural extension workers, NGOs, and farmer forums. The study highlights the importance of strengthening community-based internal capacity and policy support that integrates local knowledge into climate adaptation strategies